DRUG EVALUATION – AYURVEDIC PERSPECTIVE W.S.R. TO VIRYA - Attampilly Preethy Sadanandan (International Journal of Applied Ayurved Research, 2019)
Ayurvedic perspective of drug evaluation means finding out ‘Ayurvedic Biodata’ or ‘Rasapanchaka’ of a drug, with which the pharmacological action of a drug can be pre-dicted. This is needed because of two important concerns – first, most of our nighantus have difference of opinion about the rasa, guna, virya and vipaka of several drugs and this has resulted in controversies. Second major problem in front of us is nothing but drug crisis and subsequent issues. For this, new drugs have to be incorporated to Ayurvedic Materia Medica and exploring the ‘ayurvedic biology’ is essential to predict their pharmacological action of which virya is the most important one.As such, thousands of researches are being conducted on herbs, but, only very less attention is being paid to the validation of drug action on the basis of ayurvedic principles. As it is known, Ayurveda is a holistic science and so making objectivity for the basic concepts like virya requires continuous interface between Ayurveda and conventional medicine. At present there are no fixed and well accepted criteria to assess the virya of a drug. This paper is an endeavor to propose some methods which can be tried to fix an objectivity for the virya of a drug, on the basis of principles of Ayurveda with the aid of modern parameters.